2012
DOI: 10.1371/journal.pone.0038569
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of the Tap42-Regulated Protein Phosphatase 2A (PP2A) Family in Wing Imaginal Disc Development of Drosophila melanogaster

Abstract: Protein ser/thr phosphatase 2A family members (PP2A, PP4, and PP6) are implicated in the control of numerous biological processes, but our understanding of the in vivo function and regulation of these enzymes is limited. In this study, we investigated the role of Tap42, a common regulatory subunit for all three PP2A family members, in the development of Drosophila melanogaster wing imaginal discs. RNAi-mediated silencing of Tap42 using the binary Gal4/UAS system and two disc drivers, pnr- and ap-Gal4, not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Overexpression of the inhibitor of matrix metalloproteases ( Timp ) results in pupal lethality and cleft thorax (Srivastava et al 2007). Finally, wing disc-specific knockdown of Tap42, a key regulator of protein phosphatases, gives rise to cleft thorax and to wing abnormalities similar to some that we observed ( Wang et al 2012 ).…”
Section: Discussionsupporting
confidence: 82%
“…Overexpression of the inhibitor of matrix metalloproteases ( Timp ) results in pupal lethality and cleft thorax (Srivastava et al 2007). Finally, wing disc-specific knockdown of Tap42, a key regulator of protein phosphatases, gives rise to cleft thorax and to wing abnormalities similar to some that we observed ( Wang et al 2012 ).…”
Section: Discussionsupporting
confidence: 82%
“…Mutants of lowfat have shorter, rounder wings in Drosophila (Hogan et al, 2011; Mao et al, 2009), whereas dok mutants have shrivelled wings (Biswas et al, 2006). The knirps‐related protein ( knrl ) is involved in second wing vein development (Table 3, Lunde et al, 2003), and Tap42 (Figure 4b) triggers apoptosis in the developing wing discs (Wang et al, 2012). Thus, we have identified some promising genes that could be studied further in this system in future.…”
Section: Discussionmentioning
confidence: 99%
“…The knirps-related protein (knrl) is involved in second wing vein development (Table 3, Lunde et al, 2003), and Tap42 (Fig. 4B) triggers apoptosis in the developing wing discs (Wang et al, 2012). Interestingly, a recent study found that knockdowns of fat and knirps affected wing shape in D. melanogaster, which regulate two of our candidate genes (Table 3, Pitchers et al, 2019).…”
Section: Candidates Genes Associated With Wing Shape Variation In Othmentioning
confidence: 91%